2005
DOI: 10.1029/2004gb002429
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal wastes: Implications for atmospheric N2O and NOx

Abstract: [1] More than 220 Tg N are processed annually through the global agriculture/animal/ human food chain. It is suggested that aerobic denitrification, reduction of nitrite formed in the first stage of nitrification, is an important source not only of global N 2 O but also of NO x . A simple top-down method indicates a globally averaged yield of 2% for N 2 O emitted as a consequence of human disturbances to the global nitrogen cycle. This yield can account not only for the contemporary budget of atmospheric N 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Although these errors are within the uncertainty range assigned below for top‐down emissions, they are nontrivial suggesting the need of better understanding lightning NO x over China. It has been suggested further that the microbial source of NO x at northern midlatitudes should be increased by a factor of 2 in GEOS‐Chem [ McElroy and Wang , 2005; Jaeglé et al , 2005], corresponding to about a 30% increase in total NO x sources over the same region. Another sensitivity test was implemented in which the background columns over east China assumed in GOME TVCs were increased by 30% relative to the GEOS‐Chem simulation.…”
Section: Seasonal Variability Of Gome‐derived Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these errors are within the uncertainty range assigned below for top‐down emissions, they are nontrivial suggesting the need of better understanding lightning NO x over China. It has been suggested further that the microbial source of NO x at northern midlatitudes should be increased by a factor of 2 in GEOS‐Chem [ McElroy and Wang , 2005; Jaeglé et al , 2005], corresponding to about a 30% increase in total NO x sources over the same region. Another sensitivity test was implemented in which the background columns over east China assumed in GOME TVCs were increased by 30% relative to the GEOS‐Chem simulation.…”
Section: Seasonal Variability Of Gome‐derived Emissionsmentioning
confidence: 99%
“…Our focus on the seasonal variability of emissions was framed in order to refine our understanding of the microbial source of NO x over China. McElroy and Wang [2005] proposed that reduction of nitrite by nitrifying bacteria under low oxygen conditions could provide a significant source of NO x and suggested that this source had been significantly underestimated in contemporary models of tropospheric chemistry. The temporal coverage of their study, however, was limited to spring [ Wang et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows that the model significantly underestimates the magnitude of the enhancements observed by MOPITT, in particular in the plume associated with export in the typhoon. Second, the model might be underestimating Asian anthropogenic and soil NO x emissions [ Wang et al , 2004; McElroy and Wang , 2005; Martin et al , 2006]. Jaeglé et al [2005] found that during summer, emissions from soils over Asia account for almost as much NO x as emissions from anthropogenic combustion sources, and that the inventory used by GEOS‐Chem underestimates this soil source by a factor of 2.…”
Section: Asian Plumesmentioning
confidence: 99%
“…NO x emissions from biomass burning and aircraft are held constant given their relatively small contribution. Soil NO x emissions specified using the Yienger and Levy (1995) scheme are thought to be too low by a factor of 2-3 (Wang et al, 2004Jaégle et al, 2005;Zhao and Wang, 2009) in China, due likely to an underestimate of the sources associated with fertilization and human/animal food chain (Wang et al, 2004;McElroy and Wang, 2005). They are doubled therefore for purposes of the top-down constraint.…”
Section: Ratio To Daily Meanmentioning
confidence: 99%